Effect of Tellurite-Mediated Oxidative Stress on the Escherichia Coli Glycolytic Pathway - Vasquez-Guzman, C; Pavez-Irrazabal, J; Pavez-Irrazabal, J (2012)
To unveil the metabolic impact of tellurite in the bacterial cell, the effect of this toxicant on the expression and activity of key enzymes of the Escherichia coli glycolytic pathway was analyzed. E. coli exposure to tellurite results in: (i) increased glucose consumption, which was paralleled by an increased expression of the glucose transporter-encoding gene ptsG, (ii) augmented phosphoglucoisomerase activity and pgi transcription, (iii) decreased activity of the enzymatic regulators phosphofructokinase and pyruvate kinase. In spite of these observations, increased intracellular pyruvate, phosphoenol pyruvate and phosphorylated sugars was observed. E. coli lacking key glycolytic enzymes was considerably more sensitive to tellurite than the parental, isogenic, wild type strain. Taken together, these results suggest that increasing the availability of key metabolites (pyruvate, phosphoenol pyruvate, NADPH), required to respond to tellurite mediated-stress, E. coli shifts the carbon flux towards the pentose phosphate pathway thus facilitating the functioning of the Entner-Doudoroff pathway and/or the glycolytic productive phase. © Springer Science+Business Media, LLC. 2012.